2021
DOI: 10.1007/s10068-021-00958-0
|View full text |Cite
|
Sign up to set email alerts
|

Mori Cortex Radicis extract inhibits human norovirus surrogate in simulated digestive conditions

Abstract: Norovirus is a major cause of acute gastroenteritis globally, resulting in enormous health and societal costs. In this study, the antiviral activities of Mori Cortex Radicis (MCR) extract and its bioactive flavonoids, morusin and kuwanon G, were tested against murine norovirus (MNV), a human norovirus surrogate, using plaque assay. The antiviral activity was confirmed in simulated digestive conditions, including simulated saliva fluid (SSF), simulated gastric fluid (SGF), and simulated intestinal fluid (SIF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…[ 22 ] The active compounds found in Mori Cortex, such as Moracin A and Morusin, endow it with distinct pharmacological characteristics, highlighting its significance in TCM treatments. [ 23 ] Therefore, this study explores the anti-OS mechanism of Mori Cortex and its main active component, Morusin, using network pharmacology and in vitro experimental methods.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] The active compounds found in Mori Cortex, such as Moracin A and Morusin, endow it with distinct pharmacological characteristics, highlighting its significance in TCM treatments. [ 23 ] Therefore, this study explores the anti-OS mechanism of Mori Cortex and its main active component, Morusin, using network pharmacology and in vitro experimental methods.…”
Section: Discussionmentioning
confidence: 99%
“…Many natural products with promising antiviral activities in vitro display reduced activity against NV under gastrointestinal conditions [ 33 , 34 ]. Mori Cortex Radicis, aged-green tea extract, and blueberry proanthocyanidins also reduce MNV titers under simulated conditions [ 21 , 33 , 34 ]. It has been reported that MNV capsid proteins are sensitive to the presence of bile, Mg 2+ , and Ca 2+ , and that at low pH—at which they are induced to contract between the P and the S domains—they enhance receptor binding [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…MNV-1 was kindly provided by Dr. Herbert Virgin (Vir Biotechnology, San Francisco, CA, USA). MNV was replicated and purified as previously reported [ 21 ]. The purified MNV suspension was stored as aliquots at −80 °C until its use.…”
Section: Methodsmentioning
confidence: 99%